Antibacterial Activity of Gallic Acid from the Leaves of Altingia excelsa Noronha to Enterococcus faecalis - Anwar, Risyandi; Hajardhini, Puspita (Open Access Macedonian Journal of Medical Sciences, 2022)
AIM : The aim of this study was to determine the antibacterial compound of Altingia excelsa leaves to inhibit the growth of Entrococcus faecalis. METHODS : The study was true experimental laboratory design. Separating the ethyl acetate extract via their compounds using various chromatographic techniques. Four extracts from A. excelsa leaves was obtained by the maceration method. The highest inhibitory effect was then continued to be isolated until one compound was obtained. Therefore, additional assay to determine chemical structure of compounds was done using UV spectra, infrared (IR), core magnetic resonance (NMR), and comparison with spectra data from the literature. The data were analyzed by ANACOVA assay. RESULTS : The highest inhibitory effect was the ethyl acetate extract. The chemical structure of compound 1 was identified as an acidic compound 3,4,5 -trihydroxy benzoate, namely as the gallic acid which had inhibitory effect against Enterococcus faecalis. Antibacterial test against Enterococcus faecalis was done to determine inhibitory effect by its compound and MIC values showed of 12.25 µg/mL. CONCLUSION : Gallic acid as the compound of Altingia excelsa leaves had a strong inhibitory effect to Enterococcus faecalis.